Associations of Interpersonal Trauma, Distress Intolerance, and Posttraumatic Stress Symptoms With Recent Problem Opioid Use in a Non-Clinical Sample of Women - Cole, Jennifer (Journal of drug issues, 2025)
Exposure to potentially traumatic events (PTE), higher rates of Posttraumatic Stress Disorder (PTSD) and higher distress intolerance have been associated separately with opioid misuse in clinical samples. Adult women who reported past year misuse of a prescription drug were recruited on Prolific Academic (ProA) to participate in an online survey (n = 154). Measures included the Trauma History Questionnaire (THQ) for lifetime trauma histories, PTSD Checklist for DSM-5 (PCL-5), Distress Intolerance (DI), NIDA-Modified ASSIST, and the Drug Abuse Screening Test (DAST-10). In a multinomial logistic regression model, experiencing a potentially traumatic event involving interpersonal victimization, having higher distress intolerance, and having greater PTSD symptoms, were significantly associated with drug use class. In particular, higher distress intolerance was associated with problem opioid use relative to problem use of other drugs. Distress intolerance is a potentially salient and modifiable target for mental health and substance use interventions.